Metastatic Salivary Duct Carcinoma with ERBB2 Amplification and Sequential Response to Ado-Trastuzumab Emtansine and Neratinib: A Case Report - Nora Asper; Kersten Sven Roth; Thomas Frank Hany; Sacha Pierre Salzberg; Marianne Tinguely; Yannick Kadvany; Andreas Trojan (Case Reports in Oncology, 2023)
Introduction: Salivary duct carcinoma (SDC) is an aggressive and rare subtype of salivary gland carcinoma. Surgical excision and radiotherapy are standard of care for early cancer. Chemotherapies with taxanes and platinum show overall response rates between 39% and 50%. SDCs are often associated with an overexpression of the androgen receptor (AR) and HER2/neu which have recently become druggable targets. Case Presentation: Here, we report on an 84-year-old male patient with metastatic SDC of the right parotid gland. In 2017, he underwent a right total parotidectomy, a right neck dissection, and an infratemporal fossa clearance followed by 6 weeks of radiotherapy. In 2018, due to metastatic spread in the lungs, bones, and pararenal gland, a pathological workup of the tumor tissue was performed and revealed both AR and HER2 overexpression, respectively. Consequently, he underwent androgen deprivation therapy and, due to asymptomatic progression, sequentially human epidermal growth factor receptor 2 (HER-2)-targeted therapy with ado-trastuzumab emtansine and neratinib, which led to stable disease during the course of about 18 months. The electronically captured patient-reported outcome had demonstrated a good tolerance of all three therapeutic lines. Conclusion: In conclusion, since effective standard therapeutic treatment options for SDC may often not be tolerable in older patients, the implementation of personalized and adaptive treatments, especially in patients with rare tumor types, might offer valuable treatment options.